A guanidine-lutetium formate second-order nonlinear optical crystal material and its preparation and application

By developing the second-order nonlinear optical crystal material of insteinforester formate [C(NH2)3]Lu(HCOO)4, the existing ultraviolet nonlinear optical crystal material has been solved, and the large birefringence and wide transmission range has been achieved, which is suitable for laser frequency conversion and photoelectric modulation and other fields.

CN119061483BActive Publication Date: 2025-04-01TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411079461.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-04-01
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

Existing ultraviolet nonlinear optical crystal materials have problems such as laser frequency conversion and photoelectric modulation, such as insufficient birefringence and short laser life, making it difficult to achieve effective ultraviolet laser output.

Method used

A second-order nonlinear optical crystal material of instearyngeal formate [C(NH2)3]Lu(HCOO)4 was developed, and the crystal material was prepared by a synthetic method, with a large birefringence and a wide transmission range, and the ultraviolet absorption cut-off edge was 220 nm.

Benefits of technology

Under 1064nm laser irradiation, the powder SHG coefficient of this crystal material is 1.1 times that of KH2PO4, achieving phase matching and having a large birefringence value of 0.106@546nm, which is suitable for the preparation of birefringence optical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119061483B_ABST
    Figure CN119061483B_ABST
Patent Text Reader

Abstract

The present invention relates to a guanidine formate lutetium second-order nonlinear optical crystal material and its preparation and application. The chemical formula of the crystal material is [C(NH2)3]Lu(HCOO)4, which belongs to the orthorhombic system, the space group is P212121, the unit cell parameters are #imgabs0#α=β=γ=90°, Z=4, and the unit cell volume is #imgabs1#. Compared with the prior art, the crystal [C(NH2)3]Lu(HCOO)4 of the present invention is simple to grow, and it is easy to obtain a millimeter-level single crystal. Under 1064nm laser irradiation, the powder SHG coefficient is 1.1 times that of KH2PO4(KDP), and phase matching can be achieved under 1064nm laser irradiation. The crystal material has a wide transmission range in ultraviolet-visible light, and the ultraviolet absorption cutoff edge is 220nm, and has broad application prospects in the field of ultraviolet and visible light lasers. In addition, the crystal has a large birefringence value, and the birefringence at 546nm is 0.106.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical crystal materials and relates to a guanidine-lutetium formate second-order nonlinear optical crystal material and a preparation method and application thereof. Background Art

[0002] Nonlinear optical crystal materials with second harmonic (SHG) characteristics have important applications in precision manufacturing such as laser frequency conversion, micromachining, optoelectronic modulation, lithography, and semiconductor detection, because they can generate continuously tunable coherent light. Nonlinear optical (NLO) crystal materials with second harmonic (SHG) characteristics have important applications in precision manufacturing such as laser frequency conversion, 193 lithography, optoelectronic modulation, and semiconductor detection, because they can generate continuously tunable coherent light. However, ultraviolet solid lasers cannot achieve effective ultraviolet laser output because the working medium usually has a short laser life. To obtain ultraviolet laser output, the best way is to achieve laser frequency conversion through ultraviolet nonlinear optical crystals with good performance. Therefore, research on ultraviolet nonlinear optical crystal materials at home and abroad has been very active and has made great progress. With the development of technology and the increase in demand, it is necessary to continuously develop new types of ultraviolet nonlinear crystals.

[0003] The birefringence of crystals is an important optical performance parameter of nonlinear optical crystal materials. The characteristics of birefringent crystals can be used to obtain linear polarized light and achieve the displacement of light beams, making birefringent crystals the key materials for making optical components such as fiber optical isolators, circulators, beam shifters, Glan prisms, optical polarizers and optical modulators in optical communications. Commonly used birefringent materials include CaCO3 crystals, TiO2 crystals, LiNbO3 crystals, YVO4 crystals, α-BaB2O4 crystals and MgF2 crystals. For TiO2 crystals, although it has a large refractive index, its light transmission range is narrow and it is difficult to use in the ultraviolet band; while MgF2 crystals have a wide transmission range, but their major defect is that their birefringence is too small and they are not suitable for use as polarization devices. With the development of society, the demand for birefringent crystals is increasing, and the quality requirements are getting higher and higher. Therefore, the discovery of new nonlinear optical crystal materials with large birefringence is still a problem to be solved.

[0004] At the same time, to test the basic physical properties (including nonlinear optical properties) of a second-order nonlinear optical crystal, the size of the crystal needs to reach the millimeter level. Therefore, developing a method to grow large-sized nonlinear optical crystals is also a very important task. At present, there are no research reports on guanidine formate lutetium optical materials. Summary of the invention

[0005] The purpose of the present invention is to provide a guanidine formate lutetium second-order nonlinear optical crystal material and its preparation and application, wherein the powder SHG coefficient under 1064nm laser irradiation is 1.1 times that of KH2PO4 (KDP), and phase matching can be achieved under 1064nm laser irradiation. In addition, the crystal material has a wide transmission range and large birefringence in ultraviolet-visible light, an ultraviolet absorption cutoff edge of 220nm, and a birefringence of 0.106@546nm, and has broad application prospects in the field of ultraviolet and visible light lasers.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] In one aspect, the present invention provides a guanidine formate lutetium second-order nonlinear optical crystal material, the chemical formula of which is [C(NH2)3]Lu(HCOO)4, belonging to the orthorhombic crystal system, the space group is P212121, and the unit cell parameters are α=β=γ=90°, Z=4, the unit cell volume is

[0008] Furthermore, the ultraviolet absorption cutoff edge of the second-order nonlinear optical crystal material is 220 nm.

[0009] The crystal structure of [C(NH2)3]Lu(HCOO)4 of the present invention is as follows: 3+ The eight O atoms from the seven [HCOO] groups coordinate to form [LuO8] polyhedra, which are connected by formate ions to form a three-dimensional framework structure of [Lu(HCOO)4]. The [C(NH2)3] ions fill the gaps in the framework structure to form the final three-dimensional framework structure.

[0010] On the other hand, the present invention also provides a method for preparing guanidine-lutetium formate second-order nonlinear optical crystal material, comprising mixing a guanidine source, a lutetium source and formic acid to obtain an initial mixed raw material, and crystallizing the raw material to obtain a target product.

[0011] Furthermore, the guanidine source is guanidine carbonate.

[0012] Furthermore, the lutetium source is lutetium nitrate.

[0013] Furthermore, the molar ratio of the guanidine source, lutetium source and formic acid in the initial mixed raw material is (0.5-50):(0.5-50):(20-100), preferably (1-10):(1-10):(20-100), more preferably 1:(1-10):(20-100), and most preferably 1:(1-2):(20-100).

[0014] Furthermore, the crystallization temperature is 100-150°C, and the time is not less than 24 hours.

[0015] Furthermore, after the crystallization is completed, the temperature is lowered to room temperature at a rate of 0.5 to 15°C / h.

[0016] In the third aspect, the present invention also provides an application of a guanidine formate lutetium second-order nonlinear optical crystal material in laser frequency conversion, photoelectric modulation, and laser signal holographic storage. Specifically, the crystal material is used for ultraviolet laser frequency conversion output. The [C(NH2)3]Lu(HCOO)4 crystal material has a large frequency doubling effect. Under 1064nm laser irradiation, its powder frequency doubling effect is about 1.1 times that of KH2PO4 crystal, and it is type I phase matching. In addition, the ultraviolet absorption cutoff edge of the crystal material is 220nm. Therefore, the crystal material has broad application prospects in the field of nonlinear optics.

[0017] In a fourth aspect, the present invention also provides an application of a guanidine formate lutetium second-order nonlinear optical crystal material in a birefringent device. Specifically, the material has a large birefringence of 0.106@546nm, so the crystal material has application prospects in birefringent optical devices.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] (1) The present invention provides a new inorganic crystal material [C(NH2)3]Lu(HCOO)4, which has a large frequency doubling effect, which is about 1.1 times the frequency doubling intensity of KH2PO4 crystal under 1064nm laser irradiation, and can achieve type I phase matching. In addition, the ultraviolet absorption cutoff edge of the crystal material is 220nm, which can be used to output ultraviolet and visible laser beams as doubled frequency harmonics, and has broad application prospects in the fields of laser frequency conversion, optoelectronic modulation, and laser signal holographic storage;

[0020] (2) The present invention provides a method for preparing the [C(NH2)3]Lu(HCOO)4 mm-sized crystals, which adopts a solvothermal method with mild reaction conditions, and can obtain high-purity crystalline samples at a high yield through crystallization at a temperature of 100-150°C, and the length of the produced crystals can reach 3.8 mm. The method is simple, the conditions are mild, and it is conducive to large-scale industrial production;

[0021] (3) The [C(NH2)3]Lu(HCOO)4 crystal material of the present invention has a large birefringence value of 0.106@546nm and can be used to prepare birefringent optical devices. It has application prospects in polarizing prisms, bit delay devices and electro-optical modulation devices for various purposes. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1This is a crystal photo of [C(NH2)3]Lu(HCOO)4;

[0023] Figure 2 It is a schematic diagram of the crystal structure of [C(NH2)3]Lu(HCOO)4;

[0024] Figure 3 is a comparison of X-ray diffraction patterns; (a) is the pattern obtained by X-ray diffraction test after sample 1# is ground into powder; (b) is the X-ray diffraction pattern obtained by simulation based on the crystal structure of sample 1# analyzed according to single crystal X-ray diffraction data;

[0025] Figure 4 is the UV-Vis-NIR transmission spectrum of sample 1#;

[0026] Figure 5 It is the infrared spectrum (2.5-25 μm) spectrum of sample 1#;

[0027] Figure 6 This is the thermogravimetric analysis spectrum of sample 1#;

[0028] Figure 7 It is the second harmonic signal diagram of sample 1# and KH2PO4 sample with size ranging from 105 to 150 μm;

[0029] Figure 8 This is the second harmonic phase matching diagram of sample 1# in the 1.064μm band;

[0030] Fig. 9 This is the birefringence test chart of sample 1# at 546nm;

[0031] Fig.10 is the thickness of sample 1#. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0033] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0034] Embodiment 1:

[0035] The guanidine source, lutetium source and formic acid are mixed into the starting materials in a given ratio, sealed in a reactor lined with polytetrafluoroethylene, heated to the crystallization temperature, kept constant for a period of time, and then slowly lowered the temperature of the reaction system to room temperature at a rate of 5°C / h. After filtering and washing, well-grown, transparent block-shaped [C(NH2)3]Lu(HCOO)4 crystals can be obtained. Among them, samples 1#-4# are all crystals of about 0.8mm in length, the maximum length of the crystal in sample 5# can reach 1.5mm, and the maximum length of the crystal in sample 6# can reach 3.8mm (such as Figure 1 shown).

[0036] The relationship between the types and proportions of the raw materials in the initial mixture, the crystallization temperature, the crystallization time and the sample number is shown in Table 1. In the table, the concentration of HCOOH is specifically 98 wt %.

[0037] Table 1 Correspondence between samples, raw materials and synthesis conditions

[0038]

[0039]

[0040] Example 2 Crystal structure analysis

[0041] The structures of samples 1# to 6# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.

[0042] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The crystal size is 0.12×0.29×0.15mm 3 ; The data collection temperature is 293K, and the diffraction light source is graphite monochromatized Mo-Kα rays ( ), the scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the SHELXTL-97 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.

[0043] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current were 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit were 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range was 5–70°, and the scanning step was 0.02°.

[0044] Among them, the single crystal X-ray diffraction test results show that samples 1#~6# have the same chemical formula and crystal structure, the chemical formula is [C(NH2)3]Lu(HCOO)4, belongs to the orthorhombic crystal system, its space group is P212121, and the unit cell parameters are α=β=γ=90°, Z=4, the unit cell volume is

[0045] Take sample 1# as a typical example, its crystal structure data is α=β=γ=90°, Z=4, the unit cell volume is Its crystal structure is Figure 2 shown.

[0046] The powder X-ray diffraction test results show that in the XRD spectra of samples 1# to 6#, the peak positions of each sample are basically the same, but the peak intensities are slightly different.

[0047] Take sample 1# as a typical example. Figure 3 shown. Figure 3 The spectrum obtained by X-ray diffraction test after sample 1# in (a) was ground into powder is similar to Figure 3 In (b), based on the crystal structure analyzed by single crystal X-ray diffraction, the simulated X-ray diffraction pattern has consistent peak positions and peak intensities, indicating that the obtained sample has high purity.

[0048] Example 3 UV transmission spectrum test

[0049] The transmission spectrum test of sample 1# was conducted on a Cary 5000 UV-Vis-NIR spectrophotometer from Agilent Technologies, USA. Figure 4 As shown by Figure 4 It can be seen that the compound has a wide optical transmittance range, the ultraviolet absorption cutoff edge is 220nm, and the corresponding optical band gap is 5.64eV.

[0050] Example 4 Infrared spectrum test

[0051] The infrared spectrum test of sample 1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows: Figure 5 shown.

[0052] Example 5 Thermogravimetric Test

[0053] The thermogravimetric test of sample 1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. The results are shown in the figure below. Figure 6 As shown by Figure 6 It can be seen that the compound can be stable to 260°C and has good thermal stability.

[0054] Example 6 Frequency doubling test experiment and results

[0055] The frequency doubling test experiment of sample 1# is as follows: a laser with a wavelength of 1064nm generated by a Q-switched Nd:YAG solid laser is used as the fundamental frequency light to irradiate the tested crystal powder, a photomultiplier tube is used to detect the generated second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the control sample KH2PO4 crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve. The particle size ranges are less than 26, 26-50, 50-74, 74-105, 105-150, 150-200, and 200-280μm. Observe the trend of the frequency doubling signal intensity changing with the particle size to determine whether it can achieve phase matching. Under the same test conditions, compare the second harmonic intensity generated by the sample and the KH2PO4 sample to obtain the relative size of the sample frequency doubling effect.

[0056] The test results show that the compound [C(NH2)3]Lu(HCOO)4 crystal has a large frequency-doubled effect. Under 1064nm wavelength laser irradiation, the frequency-doubled signal intensity is 1.1 times that of the control sample KH2PO4 crystal (such as Figure 7 ), which can achieve type I phase matching (such as Figure 8 ).

[0057] Example 7 Birefringence Test Experiment and Results

[0058] The birefringence test experiment of sample 1# is as follows: The birefringence of [C(NH2)3]Lu(HCOO)4 crystal is evaluated by a ZEISS Axio Scope 5 polarizing microscope equipped with a Berek compensator under a 546nm light source. According to the formula R = |N e -N o |×T=Δn×T to measure its birefringence. Among them, the optical path difference is R, the measured birefringence is Δn, and the crystal thickness is T. The test results show that when the [C(NH2)3]Lu(HCOO)4 crystal is completely extinct, the optical path difference is 3.29μm (such as Fig. 9 ). The thickness of [C(NH2)3]Lu(HCOO)4 crystal is 31μm (such as Fig.10 ). According to the formula R = Δn × T, the birefringence of [C(NH2)3]Lu(HCOO)4 crystal is 0.106.

[0059] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A guanidine-lutetium formate second-order nonlinear optical crystal material, characterized in that: Its chemical formula is [C(NH2)3]Lu(HCOO)4, it belongs to the orthorhombic crystal system, the space group is P212121, and the unit cell parameters are α=β=γ=90°, Z=4, the unit cell volume is 2. The guanidine formate lutetium second-order nonlinear optical crystal material according to claim 1, characterized in that: Its ultraviolet absorption cut-off edge is 220nm.

3. The method for preparing a guanidine formate lutetium second-order nonlinear optical crystal material according to claim 1 or 2, characterized in that: A guanidine source, a lutetium source and formic acid are mixed to obtain an initial mixed raw material, which is crystallized to obtain a target product.

4. The method for preparing a guanidine formate lutetium second-order nonlinear optical crystal material according to claim 3, characterized in that: The guanidine source is guanidine carbonate.

5. The method for preparing a guanidine formate lutetium second-order nonlinear optical crystal material according to claim 3, characterized in that: The lutetium source is lutetium nitrate.

6. The method for preparing a guanidine formate lutetium second-order nonlinear optical crystal material according to claim 3, characterized in that: The molar ratio of the guanidine source, the lutetium source and the formic acid in the initial mixed raw material is (0.5-50):(0.5-50):(20-100).

7. The method for preparing a guanidine formate lutetium second-order nonlinear optical crystal material according to claim 3, characterized in that: The crystallization temperature is 100-150°C and the time is not less than 24 hours.

8. The method for preparing a guanidine-lutetium formate second-order nonlinear optical crystal material according to claim 7, characterized in that: After crystallization is completed, the temperature is cooled to room temperature at a rate of 0.5 to 15°C / h.

9. Application of the guanidine formate lutetium second-order nonlinear optical crystal material as claimed in claim 1 or 2 in laser frequency conversion, photoelectric modulation and laser signal holographic storage.

10. Use of the guanidine formate lutetium second-order nonlinear optical crystal material as claimed in claim 1 or 2 in laser frequency converters, polarizing prisms, delay devices, birefringent optical devices and electro-optical modulation devices.

Citation Information

Patent Citations

  • Iodate cerium sulfate second-order nonlinear optical crystal and preparation and application thereof

    CN113417008A

  • Nonlinear optical element and nonlinear optical material

    JP1996328057A